PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM GAME TOURNAMENT (TGT) TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPAS DI KELAS IV SEKOLAH DASAR - Delvita Syahputri; Jumat Barus; Samsul Bahri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine the effect of applying the cooperative learning model of the Team Game Tournament (TGT) type on the science and social studies (IPAS) learning outcomes of fourth-grade students at SD Negeri 2 Semadam, particularly on the topic of the influence of force on the motion of objects. The background of this research is the low learning outcomes of students taught through the Discovery Learning model commonly used by the teacher, where only 40% of students reached the minimum mastery criterion. A quantitative approach with a quasi-experimental method and a Nonequivalent Control Group Design was employed, involving 48 fourth-grade students divided into an experimental class (24 students) taught using TGT and a control class (24 students) taught using Discovery Learning. Data were collected through a multiple-choice achievement test administered as a pretest and posttest, which had been tested for validity and reliability. Data analysis included descriptive statistics, normality and homogeneity tests, and an independent sample t-test using SPSS version 27. The results show that the average posttest score of the experimental class (79.17) was higher than that of the control class (70.42). The independent sample t-test produced a significance value of 0.009 (p < 0.05), indicating that the null hypothesis was rejected. It is concluded that the application of the TGT cooperative learning model has a significant effect on the IPAS learning outcomes of fourth-grade elementary school students.